Pengembangan Pengembangan Prototipe Sistem Keamanan Pintu Menggunakan Sensor Sentuh Dan Verifikasi Password Berbasis IoT: Pengembangan Prototipe Sistem Keamanan Pintu Menggunakan Sensor Sentuh Dan Verifikasi Password Berbasis IoT - Ahmad Khairul Anam; Lalu Delsi Samsumar; Zaenudin, Zaenudin; Ardiyallah Akbar; Muh Nasirudin Karim (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
The development of door security technology has grown rapidly, but in Housing, the majority of people still use conventional keys that are vulnerable to theft and duplication. This study aims to develop a prototype door security system using touch sensors and password verification based on the Internet of Things (IoT) to improve security and comfort. The research method includes identifying needs through environmental observation, prototype design, development, evaluation, and prototype improvement. The results of the study show that this prototype allows users to access the door through password verification and use a touch sensor to open the door. This system is effective, easy to use, and increases security compared to conventional keys. This study shows the potential for implementing a safer and more practical IoT-based door security system, providing peace of mind for residents in Housing.